Association of interleukin-1β levels in type 2 diabetes mellitus patients - Rathore, Hemlata; Ailani, Vinita; Rathore, Brijesh (International Journal of Research in Medical Sciences, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a complex, non-communicable illness mainly marked by two main features: insulin resistance and chronic inflammation. Interleukin-1β (IL-1β) has been implicated in metabolic processes including insulin secretion and b-cell apoptosis. Increased levels of pro-inflammatory markers such as IL-1β, tumor necrosis factor-α and adipokines has been reported in T2DM patients. Recent studies have demonstrated a positive correlation between Interleukins in T2DM patients. The objective of the study was to find association of IL-1β in T2DM patients. Methods: We conducted a cross-sectional study among T2DM patients visiting the OPD of Pulmonary Medicine. T2DM patients aged between 40 to 65 years of either sex were recruited. Biochemical investigations were performed in blood sample. Results: We recruited 340 T2DM patients (162 males and 178 females) for the present study. Biochemical analysis viz. Plasma glucose and HbA1c reported 78 subjects with uncontrolled diabetes and 262 subjects with controlled diabetes. IL-1β levels were found to be significantly increased (p<0.001, t=21.76) in uncontrolled diabetics (55.23±9.11) in comparison with controlled diabetics (25.39±11.04). Conclusions: Results suggests a highly significant and positive (p<0.001) association of IL-1β with glucose levels in T2DM patients.